Effect of Composition on the Compressibility and Shear Strength of Dredged Cohesive Sediment - Barciela-Rial, Maria; Vardon, Philip J.; Van Kessel, Thijs; Griffioen, Jasper; Winterwerp, Johan C. (Frontiers in Earth Science, 2022)
Progressively more dredged sediments are being reused for engineering projects. For example, the Marker Wadden is a new wetland constructed in Lake Markermeer, the Netherlands, with dredged cohesive sediment originating from the bed of the lake. Such dredged sediments often are dominated by cohesive sediment particles with varying amounts of sand and organic matter. In addition, during as well as after the construction process the material consolidates and often is compressed from a very loose state into a significantly denser condition. To assess the mechanical behaviour of this material, the compressibility of Markermeer dredged sediment samples with various sand and organic matter contents was analysed with Incremental Loading oedometer tests, whereas the undrained shear strength was studied with the fall cone test. The behaviour was theoretically analysed assuming a fractal structure of the sediment and applying power law constitutive equations for effective stress, hydraulic conductivity and undrained shear strength. These constitutive equations, usually used at low initial sediment densities, worked well at the relatively high initial densities studied and proved to be an useful tool to identify the transition fines content TFC. The constitutive equations were put in context with indicators traditionally used in soil mechanics. Samples, each with an identical composition of the fines fraction (particles< 63 μm), but with a sand content varying from 9 to 40%, showed the same compressibility and undrained shear strength behaviour For a natural sand content of 70%, the behaviour was dominated by sand. The organic matter oxidation was observed to drastically decrease the compressibility and the shear strength and even to decrease the amount of sand needed to exhibit sand dominated behaviour, showing the importance of the reactivity or state of organic matter on the TFC.